Electrophoretic proteinogram reference interval from Argentina Northeastern captive caimans (crocodylia: Alligatoridae) - Coppo, J.A. (2006)
The purpose of the study was to establish the reference interval for serum electrophoretic proteinogram from captive Northeastern Argentinean caimans, as well as to detect physiological variations attributable to species, sex, age, feeding and year season. Samples from 223 healthy sub-adults, both sexes specimens of Caiman latirostris (n=109) and Caiman yacare (n=114), were obtained. Total protein (4.01±0.61 g/dl) was determined by spectrophotometry. Values from albumin (0.96±0.20 g/dl) and globulins alpha (0.74±0.16 g/dl), beta (0.87±0.18 g/dl) and gamma (1.39±0.27 g/dl), were obtained by electrophoresis on cellulose acetate and densitometric valuation. Presence of pre-albumin on band comprised between 20-66 kDa, were detected by electrophoresis on polyacrilamide gel. Reptile albumin registered molecular weight from 69 kDa. Protein values were higher in males than in females, being significantly higher (p<0.05) for gamma globulin. All the studied parameters were lower in C. latirostris than in C. yacare. Growing produced significant increase of total protein, albumin, and albumin/globulin ratio. On the contrary, these parameters were lower during winter. Handling and feeding systems used with farmed reptiles caused total protein and albumin values higher than those registered in zoo specimens. Obtained data are applicable for caiman?s nutritional control, as well as for diagnosis and illness prevention.